The RK processor: A program for analysing metaphor and word feature-listing data - Reid, J. Nick; Katz, Albert (Behavior research methods, 2022)
Feature-listing tasks are an invaluable resource for exploring how words, categories, and metaphors are represented. However, manually coding the generated features is time-consuming and expensive, and involves subjective judgments from the experimenter. The purpose of this paper is to introduce the “RK processor”, a program that was developed in our lab to analyse metaphor feature data but which can also be applied to other feature-listing data. After detailing the steps of processing, we demonstrate that the processed feature data align with previous findings in which metaphor features were processed manually and that the processed features predict dimensions of metaphor judgments pertaining to comprehensibility and metaphor goodness. Lastly, we present several other applications for research on word similarity, compound words, categories and concepts, semantic ambiguity, incongruity resolution and computational modelling. The RK processor offers researchers a valuable tool to save time and resources and to maintain consistency in processing.